Peri-ovulatory endocrine regulation of the prostanoid pathways in the bovine uterus at early dioestrus - Oliveira, Milena Lopes; D'Alexandri, Fabio Luiz; Pugliesi, Guilherme; Van Hoeck, Veerle; Mesquita, Fernando Silveira; Membrive, Claudia M. B. [UNESP]; Negrao, Joao Alberto; Wheelock, Craig E.; Binelli, Mario (Csiro Publishing, 2017)
We hypothesised that different endocrine profiles associated with pre-ovulatory follicle (POF) size would impact on uterine prostanoid pathways and thereby modulate the histotroph composition. Beef cows (n=15 per group) were hormonally manipulated to have small (SF-SCL group) or large (LF-LCL group) pre-ovulatory follicles (POF) and corpora lutea (CL). Seven days after induction of ovulation, animals were slaughtered and uterine tissues and flushings were collected for quantification of prostanoids. The POF and CL size and the circulating progesterone concentrations at Day 7 were greater (P<0.05) in the LF-LCL cows than in the SF-SCL group, as expected. The abundance of 5 out of 19 genes involved in prostanoid regulation was different between groups. Transcript abundance of prostaglandin F2, E2 and I2 synthases was upregulated (P<0.05) and phospholipase A2 was downregulated (P<0.05) in endometrium of the LF-LCL group. No difference (P>0.1) in prostanoid concentrations in the endometrium or in uterine flushings was detected between groups. However, prostaglandin F2 and E2 concentrations in the uterine flushings were positively correlated with the abundance of transcripts for prostaglandin endoperoxide synthase 2 (0.779 and 0.865, respectively; P<0.002). We conclude that endometrial gene expression related to prostanoid synthesis is modulated by the peri-ovulatory endocrine profile associated with POF size, but at early dioestrus differences in transcript abundance were not reflected in changes in prostanoid concentrations in the uterine tissue and fluid.
Keywords: endometrium; oestrogen; physiology; prostaglandins